IN SITU SOIL CHEMICAL AND PHYSICAL ANALYSIS OF THE SWEETEST CARABAO MANGOES OF ZAMBALES - Ma. Christel M. Galapago; David P. Pilien; Ronel S. De Guzman (American Journals Publishing, 2022)
The study was conducted to analyze some of the soil's physical and chemical properties in situ, where the sweetest carabao mangoes of Zambales were found.Soil samples in three different soil depths were taken within the canopy coverage of the sweetest carabao mangoes from San Marcelino, Masinloc, and Sta. Cruz before the analysis. The test was focused on the soil's potassium content being linked and assumed to be responsible for the sweetness of the mango fruits.As a result of the soil analysis from the three study areas, high potassium concentrations in three sampling depths from all the areas were found, particularly in Sta. Cruz. Also, a favorable pH range in all the sites and soil depths was observed and so the potassium present in the soil was presumed to be at its optimum level of availability and hence, acted in enhancing the sweetness of the fruits. Considerable amounts of nitrogen, phosphorus, calcium, and magnesium were also found in the soil, a manifestation that suggests that potassium's role in the sucrose formation was favored.Undoubtedly, the result of this study in correlation to another study on leaf tissue analysis of the same mango trees from the same sites further confirmed that potassium was the nutrient element responsible for the sweetness of the mango fruits of Zambales. The mango leaves were found to contain a high concentration of potassium absorbed from the soil leading simultaneously to the formation of fruit sugar, the prime function of potassium through metabolic processes in the mango tree.
Keywords: In situ; carabao mango; soil analysis